Astrogliosis in the Hippocampus and Cortex and Cognitive Deficits in Rats with Streptozotocin-Induced Diabetes: Effects of Melatonin - Baydas, G.; Nedzvetskii, V. S.; Kirichenko, S. V.; Nerush, P. A. (Springer, 2008)
We examined, using a Western blot technique, the contents and compositions of a specific neuronal protein, NCAM, and of an astrocyte marker, GFAP, in the hippocampus and cortex of rats with streptozotocin (STZ)-induced diabetes and compared these indices with those in control ( intact) animals and STZ-diabetic rats treated with melatonin. Behavioral cognitive indices manifested in the passive avoidance test ( PAT) and Morris water maze (MWM) learning performance were also estimated in the above groups of animals. As was found, STZ-diabetic rats demonstrated clear cognitive deficits according to the values of the retention latency in the PAT and time of reaching the escape platform in the MWM performance. In these animals, the GFAP content was elevated, and the amount of degraded products of this protein increased, as compared with the control. Simultaneously, considerable down-regulation of the NCAM expression and modifications of NCAM isoform composition were found in diabetic animals. In addition, significantly increased levels of lipid peroxidation ( according to the amounts of malondialdehyde + 4-hydroxyalkenals) were measured in the cortex and hippocampus of rats with stable diabetic hyperglycemia. All the above-mentioned shifts were significantly smoothed or even nearly completely compensated in the case of treatment of STZ-diabetic rats with melatonin ( 10 mg/kg per day). The role of diabetes-related changes in the amount and composition of specific neural and glial proteins in the development of cognitive deficits, the involvement of oxidative stress in the mechanisms of the respective shifts, and possible mechanisms of the neuroprotective effect of melatonin with respect to diabetes-related pathological biochemical and behavioral shifts are discussed.
Keywords: cognitive deficits; glial fibrillary acidic protein (GFAP); neural cell adhesion molecule (NCAM); astrogliosis; diabetes mellitus; melatonin